(untitled) (Historia, 2021)
This article discusses the Braamfontein explosion of 1896 and the chain of mistakes that led up to the blast. The explosion took place on 19 February 1986, when several trucks of dynamite exploded at Johannesburg Station after being left there for three days following a collision with a shunting train. The force of the explosion left a massive crater and practically destroyed every home and structure in the vicinity, leaving between 1500 and 3000 residents homeless. Between 80 and 100 people lost their lives but the exact number of fatalities remains unknown because many simply "disappeared". The key question here is how did the actions of those involved with the transport, delivery and sale of the dynamite lead to the explosion? The exact cause of the blast became a mystery as the Commission of Inquiry could not reach a solid conclusion. Instead it concluded that "facts and testimonies indicate the blast occurred through the negligence - jointly or severally - by the parties involved ...". This article dissects this negligence and in so doing sheds new light on the causes of the explosion and the dispute over the £3 that set off a domino effect.